Older adult experience of care and staffing on hospital and community wards: a cross-sectional study - Kirsten Barnicot; Kirsty Allen; Chloe Hood; Mike Crawford (BMC, 2020)
Abstract Background Recent major concerns about the quality of healthcare delivered to older adults have been linked to inadequate staffing and a lack of patient-centred care. Patient experience is a key component of quality care - yet there has been little research on whether and how staffing levels and staffing types affect satisfaction amongst older adult hospital inpatients. This study aimed to evaluate the association between registered nurse and healthcare assistant staffing levels and satisfaction with care amongst older adult hospital inpatients, and to test whether any positive effect of higher staffing levels is mediated by staff feeling they have more time to care for patients. Methods Survey data from 4928 inpatients aged 65 years and older and 2237 medical and nursing staff from 123 acute and community medical wards in England, United Kingdom (UK) was collected through the Royal College of Psychiatrist's Elder Care Quality Mark. The cross-sectional association between staffing ratios and older adult patient satisfaction, and mediation by staff perceived time to care, was evaluated using multi-level modelling, adjusted for ward type and with a random effect for ward identity. Results Higher numbers of patients per healthcare assistant were associated with poorer patient satisfaction (adjusted β = − 0.32, 95% CI − 0.55 to 0.10, p < 0.01), and this was found to be partially mediated by all ward staff reporting less time to care for patients (adjusted β = − 0.10, bias-corrected 95% CI − 1.16 to − 0.02). By contrast, in both unadjusted and adjusted models, the number of patients per registered nurse was not associated with patient satisfaction. Conclusions Older adult hospital patients may particularly value the type of care provided by healthcare assistants, such as basic personal care and supportive communication. Additionally, higher availability of healthcare assistants may contribute to all ward staff feeling more able to spend time with patients. However, high availability of registered nurses has been shown in other research to be vital for ensuring quality and safety of patient care. Future research should seek to identify the ideal balance of registered nurses and healthcare assistants for optimising a range of outcomes amongst older adult patients.